Flipbook-Based E-Book Development for Yogya Putri Style Bridal Makeup in the Central Indonesian Bridal Makeup Course - Syanindita Galuh Kirana; Jenny Sista Siregar; Neneng Siti Silfi Ambarwati (Jurnal Multidisiplin Sahombu, 2026)
This research is motivated by the limitations of students to learn independently and the unavailability of flipbook-based e-book for Yogya Putri Style Bridal Makeup in traditional and modified forms as learning media in certain courses. This study aims to develop a flipbook-based e-book of Yogya Putri Style Bridal Makeup in the Central Indonesia Bridal Makeup Course as a complement to student learning resources using the Canva and Heyzine applications based on an R&D (Research and Development) approach with the ADDIE development model. Data collection through literature studies, observations, interviews, and questionnaires with samples of students, lecturers, media experts and material experts. Product validation tests are carried out to assess the feasibility of the product by material experts and media experts as well as practicality tests by users. Based on the validation test of material experts stage I, a percentage score of 92.5% was obtained and the validation test of material experts stage II obtained a percentage score of 95% and the validation test of media experts stage I obtained a percentage score of 60% and the validation test of media experts stage II obtained a percentage score of 86% so that it can be categorized as "very feasible". The practicality test was conducted in three stages for undergraduate students of the 2023 intake of Makeup Education, starting with an one to one test, a small group test, and a field trial test, with scores of 92.8%, 92.9%, and 93%, respectively, categorizing it as "very practical." Therefore, it can be concluded that the flipbook-based e-book on Yogya Putri Style Bridal Makeup is feasible and practical for use as a learning medium